Prototype of Sexual Violence A Cognitive Linguistic Study - Julius Novan Deni Kurniawan (English Language and Education Spectrum, 2023)
Sexual violence is a social issue that still occurs in Indonesia. Responding to this issue, social activists urged the government to ratify the Draft Law on the Elimination of Sexual Violence proposed by the National Women’s Commission in 2016. However, as of August 2021, the Draft Law on the Elimination of Sexual Violence changed its name to the Draft Law on the Sexual Violence Crime, and there were cuts of 85 articles and from 9 to 4 categories of sexual violence. Even though it was passed on May 9, 2022, along the way, there has been controversy over the process of making this law. One controversy is the differences in the views categories between the National Women's Commission and Commission VIII DPR RI. Then by using prototype theory, we can find the categories of sexual violence in society to equalize perceptions. Data analysis uses mixed methods, which analyze data quantitatively and qualitatively. Based on the results of the analysis, it was found that there were ten classifications of sexual violence prototypes from 20 respondents, with a total of 61 data samples. The prototypes that best represent the concept of sexual violence are rape and sexual harassment, with 17 data each. Furthermore, sexual harassment and rape, the prototypes of sexual violence with each of the 17 data, are spread almost evenly across all age ranges.